The impact of increasing user charges for diabetes medicines: lessons from Finland - Rättö, Hanna; Lavikainen, Piia; Aaaltonen, Katri; Martikainen, Janne; Martinez, Marcos Gallardo; Thomson, Sarah (Spain, 2026)
Diabetes is a common chronic condition that affects around 7% of adults in
Europe. Many people with diabetes need medicines to control symptoms
and prevent complications. In 2017, against a backdrop of rising diabetes
care costs and budgetary pressure, the Finnish health system increased user
charges (co-payments) for all diabetes medicines except insulin, changing
them from a fixed co-payment of €4.50 per item to a percentage co-payment
of 35% of the retail price. What at first glance may seem like a relatively
modest change in co-payment design led to a substantial increase in outof-
pocket payments for diabetes medicines. This brief summarizes the
policy change and its impact and identifies lessons for Finland and for other
countries that are concerned about the negative effects of user charges on
access to health care.